Dao as you? Dropping proper parthood in a mereological reconstruction of Daoist metaphysics - Banka, R (Brill, 2022)
In this article, I discuss parthood status in mereologically interpreted Daoist metaphysics, based on the Daodejing. I depart from the dao and you interrelation, which mereologically overlap by sharing parts. I consider the case of a complete overlap, which (a) challenges proper parthood, according to which a part cannot be identical with the whole that it composes, and (b) entails the question of identity that, while complying with classical mereology, cannot be consistent with Daoist metaphysics. The discussion leads to abandoning proper parthood and antisymmetry axiom from classical axiomatics. It also shows a plausible further direction for mereological reconstruction.